USE OF CONDOMS FOR CUSTOMERS OF COMMERCIAL SEX WORKERS IN THE CONTEXT OF HIV / AIDS PREVENTION AT THE BATAM CITY NON-PANTI SOCIAL REHABILITATION CENTER - Indriasari Indriasari; Ronny Sutanto (Universitas Batam, 2021)
AIDS is a disease that is a global health problem after claiming more than 70 million people have been infected with the HIV virus so far. In the city of Batam in 2017, 47 people died from HIV / AIDS. Condom use behavior among sex workers and also customers is one of the efforts to prevent and control the transmission of HIV / AIDS. The purpose of this study was to determine the description of condom use among clients of commercial sex workers in the context of HIV / AIDS prevention. Method : This research is descriptive conducted at the Center for Social Rehabilitation of Non Panti Teluk Pandan Tanjung Uncang, Batam City, with a total sample of 91 commercial sex worker customers who were taken by purposive sampling. Result : The results showed. It is known that the use of condoms among CSW customers in the center of the Social Rehabilitation Center for non-Panti Kota Batam, more than half of the customers did not use condoms, namely 46 (51.1%). conclusion : It is known that the use of condoms among commercial sex workers at the center for nonPanti Panti Social Rehabilitation in Teluk Pandan Tanjung Uncang, Batam City, more than half of the customers did not use condoms, namely 46 (51.1%).